Schlüsselkompetenzen spielend trainieren Teamspiele von A-Z mit wissenschaftlicher Hinführung, Geschichte, Hintergrund - Brunner, Anne (De Gruyter Oldenbourg, 2016)
From A to Z, time-honored and ideal models are presented that have been proven in practice and are easy to organize and implement. Part 1 of the book gives a theoretical introduction to the context of the play method. Part 2 is the practical part and thus the true focus of the work
Keywords: Teamwork; Gruppenspiel